2013
DOI: 10.1016/j.transproceed.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Intent to Donate in Hispanic American High School Students: Results of a Prospective Observational Study

Abstract: Background High school students are an important target audience for organ donation education. A novel educational intervention focused on Hispanic American (HA) high school students might improve organ donation rates. Methods A prospective observational study was conducted in five Los Angeles High Schools with a high percentage of HA students. A ‘culturally sensitive’ educational program was administered to students in the 9th to 12th grades. Pre-intervention surveys that assessed awareness, knowledge, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
1
16
1
1
Order By: Relevance
“…Additionally, people diagnosed with cancer might also be interested in receiving information in order to support their families in preventing cancer or to better understand the etiology of their illness. Diagnosis of cancer in the family also leads to heightened perceptions of cancer risk and cancer worry among family members [28], which often result in CPI needs [29]. Obtaining CPI is necessary in making informed decisions about cancer prevention and can reduce anxiety [9], but only one-fifth of oncologists provide this information [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, people diagnosed with cancer might also be interested in receiving information in order to support their families in preventing cancer or to better understand the etiology of their illness. Diagnosis of cancer in the family also leads to heightened perceptions of cancer risk and cancer worry among family members [28], which often result in CPI needs [29]. Obtaining CPI is necessary in making informed decisions about cancer prevention and can reduce anxiety [9], but only one-fifth of oncologists provide this information [12].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 10 146 predominantly Hispanic American High School students (4876 pre‐ and 3812 post‐intervention) in the United States found an increase in intention to donate ( P = 0.0003) following a 45‐minute presentation of evidence‐based information. However, when adjusted for independent predictors (student school grade, Hispanic or African America race, religion, and family support), this was no longer significant . They concluded that more research is needed to identify the factors that negatively influence uptake among adolescents so that tailored interventions can be delivered …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] These all had positive results, Dr. Salim says, but he asks, "What happens next? How are we going to maintain this and keep it moving forward?"…”
Section: (Continued From Previous Page)mentioning
confidence: 99%